A modified polycaprolactone stent and preparation method thereof
By embedding bioactive ceramics in polycaprolactone scaffolds and introducing ZIF-8 surface modified polyester microspheres in composite hydrogels, combined with 3D printing technology, the existing bone tissue engineering scaffolds have solved the problems of insufficient bone regeneration and antibacterial effects, insufficient mechanical strength and complex preparation processes in promoting bone regeneration, achieving efficient bone tissue repair and regeneration.
Patent Information
- Application Number
- CN202411966893.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The existing bone tissue engineering scaffolds have insufficient bone activity in materials, difficulty in achieving the effect of promoting bone regeneration and antibacterial at the same time, insufficient mechanical strength, complex preparation process, and difficulty in industrialization.
By embedding bioactive ceramics in polycaprolactone scaffolds and introducing ZIF-8 surface modified polyester microspheres into composite hydrogels, bioactive ceramics/polycaprolactone scaffolds with porous structures are prepared in combination with 3D printing technology to enhance their biological activity and mechanical properties while imparting antibacterial properties.
The modified polycaprolactone scaffold has achieved high compressive strength, low in vitro cytotoxicity, good biosafety and long-term antibacterial effect, which is suitable for the repair and regeneration of bone tissue defects.
Smart Images

Figure BDA0005218569160000131 
Figure HDA0005218569170000011 
Figure HDA0005218569170000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bone tissue engineering scaffolds, and in particular to a modified polycaprolactone scaffold and a preparation method thereof. Background Art
[0002] 3D printing obtains three-dimensional entities by stacking raw materials layer by layer on a plane. It has penetrated into various industries due to its unique advantages of high precision, personalized manufacturing and complex shape construction. At present, the more mature 3D printing technologies include photopolymerization 3D printing, fused deposition 3D printing, inkjet 3D printing and laser sintering 3D printing. Among them, the basic principle of fused deposition 3D printing technology is that the base material is heated in the nozzle to a temperature slightly higher than its melting point. Under the action of pressure, the base material is extruded from the nozzle into filaments. The nozzle moves in three dimensions under computer control, thereby stacking the base material filaments into shape.
[0003] The ideal bone tissue engineering scaffold should also have an interconnected porous network structure to provide interconnected channels for cell migration, ion transport, and cell-to-cell interaction. In addition, in order to cope with different parts, different injury conditions and different individual differences, personalized customization is also required. Conventional bone tissue engineering scaffold preparation methods such as foaming, sacrificial template method, freeze-drying method and casting method can no longer meet the needs. 3D printing technology can freely design the porosity and shape of the scaffold, which can well meet the needs of bone tissue engineering.
[0004] Polycaprolactone (PCL) is a commonly used material for 3D printing. It has good biocompatibility, is non-toxic, and is degradable. It can also induce tissue regeneration and provide a place for cell adhesion, proliferation, and differentiation. However, when PCL is used as a raw material for 3D printing to prepare bone repair materials, the hydrophobicity of the raw material itself will affect the adhesion of the scaffold it forms, and after it degrades, its mechanical structure is significantly damaged, which cannot meet the performance requirements of bone tissue engineering scaffolds.
[0005] Hydrogels can absorb thousands of times their own weight in water and can take on almost any shape and size. Similar to natural extracellular matrices, hydrogels can encapsulate bioactive substances such as cells or growth factors. Due to the network structure of hydrogels, bioactive substances can be embedded inside the network structure and the encapsulated substances can be released in a controlled manner. In addition, hydrogels can be absorbed after degradation in the body and perfectly integrate with surrounding tissues, thus avoiding the complexity of surgical removal and reducing inflammatory responses. Therefore, hydrogels have good application prospects in bone regeneration and repair, but single hydrogels have the defect of insufficient mechanical strength.
[0006] In addition, existing bioactive 3D printed scaffolds generally have problems such as insufficient bone-promoting activity of the material, difficulty in achieving the effects of promoting bone regeneration and antibacterial at the same time, insufficient mechanical strength, complex preparation process, and difficulty in industrialization. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a modified polycaprolactone stent; the second purpose of the present invention is to provide a preparation method of the modified polycaprolactone stent.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a modified polycaprolactone scaffold, comprising the following preparation materials: polycaprolactone, bioactive ceramics, solvent I and composite hydrogel; the composite hydrogel comprises a hydrogel solution and ZIF-8 surface-modified polyester microspheres dispersed therein.
[0010] In some embodiments of the present invention, the molecular weight of the polycaprolactone is 30,000-60,000 Da.
[0011] In some embodiments of the present invention, the solvent I comprises a C1-C2 chloroalkane.
[0012] In some specific embodiments of the present invention, the solvent I comprises dichloromethane.
[0013] In some embodiments of the present invention, the bioactive ceramic is selected from at least one of hydroxyapatite, bioglass, calcium silicate, calcium carbonate, calcium sulfate, tricalcium phosphate, octacalcium phosphate, and amorphous calcium phosphate.
[0014] In the present invention, bioactive ceramics are embedded in a polycaprolactone scaffold. The bioactive ceramics include surface bioactive ceramics and bioabsorbable ceramics. The biosurface active ceramics usually contain hydroxyl groups and are porous. Biological tissues can grow into them and form a firm bond with their surface. The bioabsorbable ceramics can be partially or fully absorbed and can induce the growth of new bone in the body. By adding bioactive ceramics to the polycaprolactone system, the biological activity of the polycaprolactone scaffold can be effectively enhanced.
[0015] In some embodiments of the present invention, the ratio of the polycaprolactone, the bioactive ceramic and the solvent I is 10 g: (0.1-0.5) g: (20-250) mL.
[0016] In some specific embodiments of the present invention, the ratio of the polycaprolactone, the bioactive ceramic and the solvent I is 10 g: (0.2-0.4) g: (25-200) mL.
[0017] In some embodiments of the present invention, in the composite hydrogel, the concentration of the hydrogel solution is 10-30 mg / mL.
[0018] In some embodiments of the present invention, in the composite hydrogel, the solid-to-liquid ratio of the ZIF-8 surface-modified polyester microspheres to the hydrogel solution is (10-80) mg:1 mL.
[0019] In the present invention, zeolite imidazolate framework material (ZIF-8) is introduced into the hydrogel. ZIF-8 has the characteristics of large specific surface area, high porosity, convenient synthesis, and controllable size. It has outstanding advantages in the encapsulation and transportation of functional substances. In addition, ZIF-8 also has excellent biocompatibility. Compared with a single hydrogel, the composite hydrogel composed of a hydrogel solution and ZIF-8 surface-modified polyester microspheres dispersed therein can more effectively improve the mechanical strength of the modified polycaprolactone scaffold and enable the scaffold to quickly release Zn in the acidic microenvironment of bacterial infection. 2+ and organic ligands to exert antibacterial effects, while the slowly released Zn 2+ It can also promote bone tissue regeneration.
[0020] In some embodiments of the present invention, the composite hydrogel comprises the following preparation raw materials: hydrogel, degradable polyester, zinc salt, organic ligand, surfactant, photoinitiator, buffer, water and solvent II, wherein solvent II is the same as or different from solvent I.
[0021] In some embodiments of the present invention, the hydrogel is selected from at least one of methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chondroitin sulfate, methacrylated chitosan, methacrylated carboxymethyl chitosan, methacrylated gelatin, methacrylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate.
[0022] In the present invention, when the hydrogel is a methacrylated hydrogel, the problem that the scaffold is not conducive to cell survival in an acidic microenvironment can be avoided by utilizing its neutral solubility. When the hydrogel is sodium alginate or methacrylated sodium alginate, the bioactive ceramics in the scaffold and the divalent metal ions (such as Ca2+) released by the degradation of the ZIF-8 surface-modified polyester microspheres can be effectively prevented from oxidizing and degrading. 2+ 、Zn 2+ etc.) can cross-link sodium alginate or methacrylated sodium alginate to maintain the mechanical strength of the hydrogel.
[0023] In some embodiments of the present invention, the molecular weight of the degradable polyester is 10,000-100,000 Da.
[0024] In some specific embodiments of the present invention, the degradable polyester is selected from at least one of polylactic acid, polylactic acid-glycolic acid copolymer, polycaprolactone, poly 3-hydroxyalkanoate, poly (3-hydroxybutyrate), poly 3-hydroxybutyrate-co-3-hydroxyvalerate, polytrimethylene carbonate, and polybutylene succinate.
[0025] In some embodiments of the present invention, the zinc salt is selected from at least one of zinc nitrate, zinc sulfate, zinc chloride and zinc acetate.
[0026] In some embodiments of the present invention, the organic ligand is selected from at least one of 2-methylimidazole, benzimidazole and imidazole.
[0027] In some embodiments of the present invention, the surfactant is selected from at least one of polyvinyl alcohol, gelatin, carboxymethyl cellulose, and methyl cellulose.
[0028] In some embodiments of the present invention, the photoinitiator includes lithium phenyl (2,4,6-trimethylbenzoyl) phosphate.
[0029] In some embodiments of the invention, the buffer comprises phosphate buffered saline (PBS buffer).
[0030] In some embodiments of the present invention, the solvent II is selected from at least one of dichloromethane, chloroform, tetrahydrofuran, ethyl acetate, dioxane, 1-methyl-2-pyrrolidone and dimethyl sulfoxide.
[0031] In some embodiments of the present invention, the composite hydrogel is prepared by a method comprising the following steps:
[0032] The degraded polyester is mixed with solvent II, and added into a mixed solution of surfactant and water to obtain polyester microspheres;
[0033] The polyester microspheres are added to a mixture of an organic ligand and water, and a mixture of a zinc salt and water is added dropwise to obtain ZIF-8 surface-modified polyester microspheres;
[0034] The hydrogel is added into a mixed solution of a photoinitiator and a buffer solution to obtain a hydrogel solution, which is then mixed with the ZIF-8 surface-modified polyester microspheres to obtain the composite hydrogel.
[0035] In some embodiments of the present invention, the solid-to-liquid ratio of the degradable polyester to the solvent II is 1 mg:(5-20) mL.
[0036] In some specific embodiments of the present invention, the solid-to-liquid ratio of the degradable polyester to the solvent II is 1 mg:(5-15) mL.
[0037] In some embodiments of the present invention, the solid-liquid ratio of the surfactant to water is (0.1-5) g:100 mL.
[0038] In some specific embodiments of the present invention, the solid-liquid ratio of the surfactant to water is (0.1-4) g:100 mL.
[0039] In some embodiments of the present invention, the process of preparing polyester microspheres is assisted by stirring; the stirring speed is 200-1000 rpm and the time is 10-25 hours.
[0040] In some specific embodiments of the present invention, the process of preparing polyester microspheres is assisted by stirring; the stirring speed is 200-800 rpm and the time is 12-24 hours.
[0041] In some embodiments of the present invention, the solid-liquid ratio of the organic ligand to water is (20-50) mg:1 mL.
[0042] In some specific embodiments of the present invention, the solid-liquid ratio of the organic ligand to water is (20-45) mg:1 mL.
[0043] In some embodiments of the present invention, the solid-to-liquid ratio of the mixed solution of the polyester microspheres, the organic ligand and water is (5-35) mg:1 mL.
[0044] In some specific embodiments of the present invention, the solid-to-liquid ratio of the mixed solution of the polyester microspheres, the organic ligand and water is (5-30) mg:1 mL.
[0045] In some embodiments of the present invention, the solid-to-liquid ratio of the zinc salt to water is (3-15) mg:1 mL.
[0046] In some specific embodiments of the present invention, the solid-liquid ratio of the zinc salt to water is (3-12) mg:1 mL.
[0047] In some embodiments of the present invention, the volume ratio of the mixed solution of the organic ligand and water to the mixed solution of the zinc salt and water is (2-10):1.
[0048] In some embodiments of the present invention, in the mixed solution of the photoinitiator and the buffer solution, the content of the photoinitiator is 0.1-0.5 wt %.
[0049] In some specific embodiments of the present invention, in the mixed solution of the photoinitiator and the buffer solution, the content of the photoinitiator is 0.2-0.4 wt %.
[0050] In some embodiments of the present invention, the solid-to-liquid ratio of the mixture of the hydrogel, the photoinitiator and the buffer solution is (10-30) mg:1 mL.
[0051] The second aspect of the present invention provides a method for preparing the modified polycaprolactone scaffold according to the first aspect of the present invention, comprising the following steps:
[0052] S1, dissolving polycaprolactone in solvent I, adding bioactive ceramics to obtain a bioactive ceramic / polycaprolactone solution, and drying to obtain a bioactive ceramic / polycaprolactone film;
[0053] S2, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, and printing layer by layer to obtain a bioactive ceramic / polycaprolactone scaffold;
[0054] S3, immersing the bioactive ceramic / polycaprolactone scaffold in the composite hydrogel and solidifying it to obtain the modified polycaprolactone scaffold.
[0055] In some embodiments of the present invention, the process of preparing the bioactive ceramic / polycaprolactone solution is assisted by stirring; the stirring speed is 300-1000 rpm and the time is 45-100 hours.
[0056] In some specific embodiments of the present invention, the process of preparing the bioactive ceramic / polycaprolactone solution is assisted by stirring; the stirring speed is 400-800 rpm and the time is 48-96 hours.
[0057] In some embodiments of the present invention, the drying method is drying under natural ventilation conditions for 48-96 hours.
[0058] In some embodiments of the present invention, the drying method is drying under natural ventilation conditions for 70-80 hours.
[0059] In some embodiments of the present invention, the printing parameters include at least one of the following parameters:
[0060] 1) The needle diameter is 0.1-0.5mm;
[0061] 2) The barrel temperature is 60-100°C;
[0062] 3) The needle temperature is 60-100°C;
[0063] 4) The fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm;
[0064] 5) Printing speed is 3-15mm / s;
[0065] 6) The fiber orientation is 0°-90°;
[0066] 7) Air pressure is 300-400 kPa;
[0067] 8) The layer height of the bioactive ceramic / polycaprolactone scaffold is 80%-90% of the needle diameter.
[0068] In some specific embodiments of the present invention, the printing parameters include at least one of the following parameters:
[0069] 1) The needle diameter is 0.2-0.5mm;
[0070] 2) The barrel temperature is 65-95°C;
[0071] 3) The needle temperature is 70-100°C;
[0072] 4) The fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm;
[0073] 5) Printing speed is 4-14mm / s;
[0074] 6) The fiber orientation is 0°-90°;
[0075] 7) Air pressure is 320-400 kPa;
[0076] 8) The layer height of the bioactive ceramic / polycaprolactone scaffold is 80%-90% of the needle diameter.
[0077] In some embodiments of the present invention, the solid-liquid ratio of the bioactive ceramic / polycaprolactone scaffold to the composite hydrogel is (0.3-1.2) mg:10 mL.
[0078] In some embodiments of the present invention, the soaking time is 0.5-5 min.
[0079] In some embodiments of the present invention, the curing condition is 400-410nm blue light irradiation for 2-15s.
[0080] In some embodiments of the present invention, after the solidification, the modified polycaprolactone scaffold is placed in a refrigerator at -25°C to -20°C for freezing, and freeze-drying.
[0081] Compared with the prior art, the present invention has the following beneficial effects:
[0082] 1) The modified polycaprolactone scaffold provided by the present invention improves the bioactivity of the polycaprolactone scaffold by adding bioactive ceramics, and enhances the mechanical properties of the polycaprolactone scaffold while giving the scaffold antibacterial properties by adding a composite hydrogel containing a hydrogel solution and ZIF-8 surface-modified polyester microspheres. The obtained modified polycaprolactone scaffold has a compressive strength higher than 20 MPa, low in vitro cytotoxicity, high biosafety, no risk of hemolysis, can better induce cells to secrete alkaline phosphatase, has osteogenic activity, and can also exert a long-term antibacterial effect, and is suitable for the repair and regeneration of bone tissue defects under infection;
[0083] 2) The preparation method of the modified polycaprolactone scaffold provided by the present invention is combined with 3D printing technology to prepare a bioactive ceramic / polycaprolactone scaffold with a porous structure, and then the scaffold is immersed in a composite hydrogel containing a hydrogel solution and ZIF-8 surface-modified polyester microspheres to fill the composite hydrogel in the pores. While maintaining the mechanical strength of the scaffold, the hydrophilicity and hydrophobicity of the scaffold are further regulated to make it more suitable for regeneration and repair of bone defects. The preparation method has a simple process, low requirements on equipment, easy to obtain raw materials, low cost, and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0084] Figure 1 is the compressive strength of the brackets in Examples 1-4 and Comparative Examples 1-5;
[0085] Figure 2 is the alkaline phosphatase activity of the scaffolds in Examples 1-4 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0086] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0087] Example 1
[0088] In this embodiment, a modified polycaprolactone stent is prepared in the following steps:
[0089] S11, dissolving 10 g of polycaprolactone (molecular weight 100000 Da) in 50 mL of dichloromethane, adding 0.2 g of octacalcium phosphate, and magnetically stirring at 400 rpm for 72 h to obtain a polycaprolactone solution in which bioactive ceramics are uniformly dispersed; pouring the bioactive ceramic / polycaprolactone solution onto a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a bioactive ceramic / polycaprolactone film;
[0090] S21, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, matching a 0.2 mm diameter needle, setting the barrel temperature to 65°C, the needle temperature to 70°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 10 mm / s, the fiber orientation to 0°-90°, the air pressure to 380 kPa, the scaffold layer height to 80% of the needle diameter, and starting layer-by-layer printing at room temperature to obtain a bioactive ceramic / polycaprolactone scaffold;
[0091] S311, dissolving 1 g of polylactic acid-glycolic acid copolymer (molecular weight 30000 Da) in 10 mL of dioxane to obtain a polyester solution, adding the polyester solution to 500 mL of an aqueous solution containing 10 g of 124 type polyvinyl alcohol, stirring at 300 rpm at room temperature for 24 h, washing with water, centrifuging, and drying to obtain polyester microspheres;
[0092] S312, adding 600 mg of polyester microspheres to 30 mL of a 20 mg / mL 2-methylimidazole aqueous solution, adding dropwise 3 mL of a 10 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;
[0093] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.2 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 300 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;
[0094] S314. Soak 20 mg of the bioactive ceramic / polycaprolactone scaffold in 200 mL of the composite hydrogel, take it out after dispersion for 3 minutes, irradiate it with 400 nm blue light for 5 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0095] Example 2
[0096] In this embodiment, a modified polycaprolactone stent is prepared in the following steps:
[0097] S11, dissolving 10 g of polycaprolactone (molecular weight 60000 Da) in 200 mL of dichloromethane, adding 0.3 g of calcium sulfate, and magnetically stirring at 800 rpm for 48 h to obtain a polycaprolactone solution in which bioactive ceramics are uniformly dispersed; pouring the bioactive ceramic / polycaprolactone solution onto a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a bioactive ceramic / polycaprolactone film;
[0098] S21, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, matching a 0.4 mm diameter needle, setting the barrel temperature to 80°C, the needle temperature to 90°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 8 mm / s, the fiber orientation to 0°-90°, the air pressure to 360 kPa, the scaffold layer height to 85% of the needle diameter, and starting layer-by-layer printing at room temperature to obtain a bioactive ceramic / polycaprolactone scaffold;
[0099] S311, dissolving 1 g of polycaprolactone (molecular weight 60000 Da) in 10 mL of dioxane to obtain a polyester solution, adding the polyester solution to 500 mL of an aqueous solution containing 15 g of carboxymethyl cellulose, stirring at 500 rpm at room temperature for 18 h, washing with water, centrifuging, and drying to obtain polyester microspheres;
[0100] S312, adding 225 mg of polyester microspheres to 45 mL of a 20 mg / mL 2-methylimidazole aqueous solution, adding dropwise 12 mL of a 4 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;
[0101] S313, dissolving 300 mg of methacryloyl chondroitin sulfate in 10 mL of PBS solution containing 0.3 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 500 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;
[0102] S314. Soak 40 mg of the bioactive ceramic / polycaprolactone scaffold in 500 mL of the composite hydrogel, take it out after dispersion for 4 minutes, irradiate it with 400 nm blue light for 2 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0103] Example 3
[0104] In this embodiment, a modified polycaprolactone stent is prepared in the following steps:
[0105] S11, dissolving 10 g of polycaprolactone (molecular weight 50000 Da) in 25 mL of dichloromethane, adding 0.25 g of hydroxyapatite, and magnetically stirring at 800 rpm for 96 h to obtain a polycaprolactone solution in which bioactive ceramics are uniformly dispersed; pouring the bioactive ceramic / polycaprolactone solution onto a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a bioactive ceramic / polycaprolactone film;
[0106] S21, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, matching a 0.35 mm diameter needle, setting the barrel temperature to 75°C, the needle temperature to 70°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 14 mm / s, the fiber orientation to 0°-90°, the air pressure to 320 kPa, the scaffold layer height to 90% of the needle diameter, and starting layer-by-layer printing at room temperature to obtain a bioactive ceramic / polycaprolactone scaffold;
[0107] S311, dissolving 1 g of polylactic acid (molecular weight 10000 Da) in 5 mL of dimethyl sulfoxide to obtain a polyester solution, adding the polyester solution to 500 mL of an aqueous solution containing 0.5 g of 1799 type polyvinyl alcohol, stirring at 200 rpm at room temperature for 12 h, washing with water, centrifuging, and drying to obtain polyester microspheres;
[0108] S312, adding 600 mg of polyester microspheres to 20 mL of a 20 mg / mL 2-methylimidazole aqueous solution, adding dropwise 10 mL of a 2 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;
[0109] S313, dissolving 100 mg of methacryloyl carboxymethyl chitosan in 10 mL of PBS solution containing 0.4 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 100 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;
[0110] S314. Soak 20 mg of the bioactive ceramic / polycaprolactone scaffold in 500 mL of the composite hydrogel, take it out after dispersion for 0.5 min, irradiate it with 400 nm blue light for 10 s to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0111] Example 4
[0112] In this embodiment, a modified polycaprolactone stent is prepared in the following steps:
[0113] S11, dissolving 10 g of polycaprolactone (molecular weight 40000 Da) in 100 mL of dichloromethane, adding 0.4 g of bioglass, and magnetically stirring at 600 rpm for 72 h to obtain a polycaprolactone solution in which bioactive ceramics are uniformly dispersed; pouring the bioactive ceramic / polycaprolactone solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a bioactive ceramic / polycaprolactone film;
[0114] S21, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, matching a 0.5 mm diameter needle, setting the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 4 mm / s, the fiber orientation to 0°-90°, the air pressure to 400 kPa, the scaffold layer height to 84% of the needle diameter, and starting layer-by-layer printing at room temperature to obtain a bioactive ceramic / polycaprolactone scaffold;
[0115] S311, dissolving 1 g of poly 3-hydroxybutyrate-co-3-hydroxyvalerate (molecular weight 100000 Da) in 15 mL of chloroform to obtain a polyester solution, adding the polyester solution to 500 mL of an aqueous solution containing 20 g of gelatin, stirring at 800 rpm at room temperature for 18 h, washing with water, centrifuging, and drying to obtain polyester microspheres;
[0116] S312, adding 500 mg of polyester microspheres to 20 mL of a 25 mg / mL 2-methylimidazole aqueous solution, adding dropwise 5 mL of a 5 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;
[0117] S313, dissolving 200 mg of methacryloyl gelatin in 10 mL of PBS solution containing 0.2 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 800 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;
[0118] S314. Soak 60 mg of the bioactive ceramic / polycaprolactone scaffold in 500 mL of the composite hydrogel, take it out after dispersion for 5 minutes, irradiate it with 400 nm blue light for 8 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0119] Comparative Example 1
[0120] This comparative example prepares a modified polycaprolactone scaffold, which is different from Example 1 in that only a single hydrogel is added to the scaffold. The preparation steps are as follows:
[0121] S11, dissolving 10 g of polycaprolactone (molecular weight 100000 Da) in 50 mL of dichloromethane, adding 0.2 g of octacalcium phosphate, and magnetically stirring at 400 rpm for 72 h to obtain a polycaprolactone solution in which bioactive ceramics are uniformly dispersed; pouring the bioactive ceramic / polycaprolactone solution onto a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a bioactive ceramic / polycaprolactone film;
[0122] S21, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, matching a 0.2 mm diameter needle, setting the barrel temperature to 65°C, the needle temperature to 70°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 10 mm / s, the fiber orientation to 0°-90°, the air pressure to 380 kPa, the scaffold layer height to 80% of the needle diameter, and starting layer-by-layer printing at room temperature to obtain a bioactive ceramic / polycaprolactone scaffold;
[0123] S313, dissolving 200 mg of methacrylated sodium alginate in 10 mL of a PBS solution containing 0.2 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution;
[0124] S314. Soak 20 mg of the bioactive ceramic / polycaprolactone scaffold in the hydrogel solution of S313, take it out after dispersion for 3 minutes, irradiate it with 400 nm blue light for 5 seconds to solidify, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0125] Comparative Example 2
[0126] This comparative example prepares a modified polycaprolactone scaffold, which is different from Example 1 in that no composite hydrogel is added to the scaffold. The preparation steps are as follows:
[0127] S11, dissolving 10 g of polycaprolactone (molecular weight 100000 Da) in 50 mL of dichloromethane, adding 0.2 g of octacalcium phosphate, and magnetically stirring at 400 rpm for 72 h to obtain a polycaprolactone solution in which bioactive ceramics are uniformly dispersed; pouring the bioactive ceramic / polycaprolactone solution onto a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a bioactive ceramic / polycaprolactone film;
[0128] S21. Place the bioactive ceramic / polycaprolactone film into a 3D printing barrel, match it with a 0.2 mm diameter needle, set the barrel temperature to 65°C, the needle temperature to 70°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 10 mm / s, the fiber orientation to 0°-90°, the air pressure to 380 kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at room temperature to obtain a bioactive ceramic / polycaprolactone scaffold, which is a modified polycaprolactone scaffold.
[0129] Comparative Example 3
[0130] This comparative example prepares a modified polycaprolactone stent, which differs from Example 1 in that no bioactive ceramic is used. The preparation steps are as follows:
[0131] S21, put 10g polycaprolactone (molecular weight 100000Da) into the 3D printing barrel, match it with a 0.2mm diameter needle, set the barrel temperature to 65°C, the needle temperature to 70°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 380kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polycaprolactone scaffold;
[0132] S311, dissolving 1 g of polylactic acid-glycolic acid copolymer (molecular weight 30000 Da) in 10 mL of dioxane to obtain a polyester solution, adding the polyester solution to 500 mL of an aqueous solution containing 10 g of 124 type polyvinyl alcohol, stirring at 300 rpm at room temperature for 24 h, washing with water, centrifuging, and drying to obtain polyester microspheres;
[0133] S312, adding 600 mg of polyester microspheres to 30 mL of a 20 mg / mL 2-methylimidazole aqueous solution, adding dropwise 3 mL of a 10 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;
[0134] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.2 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 300 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;
[0135] S314, soak 20 mg of the polycaprolactone scaffold in the composite hydrogel of S313, take it out after dispersion for 3 minutes, irradiate it with 400 nm blue light for 5 seconds to solidify, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0136] Comparative Example 4
[0137] This comparative example prepares a modified polycaprolactone scaffold, which differs from Example 1 in that no bioactive ceramic is used and only a single hydrogel is added. The preparation steps are as follows:
[0138] S21, put 10g polycaprolactone (molecular weight 100000Da) into the 3D printing barrel, match it with a 0.2mm diameter needle, set the barrel temperature to 65°C, the needle temperature to 70°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 380kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polycaprolactone scaffold;
[0139] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of a PBS solution containing 0.2 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution;
[0140] S314, soak 20 mg of the polycaprolactone scaffold in the composite hydrogel of S313, take it out after dispersion for 3 minutes, irradiate it with 400 nm blue light for 5 seconds to solidify, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polycaprolactone scaffold.
[0141] Comparative Example 5
[0142] This comparative example prepares a polycaprolactone stent, and the steps are as follows:
[0143] S21, put 10g polycaprolactone (molecular weight 100000Da) into the 3D printing barrel, match it with a 0.2mm diameter needle, set the barrel temperature to 65°C, the needle temperature to 70°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 380kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polycaprolactone scaffold;
[0144] Performance Testing
[0145] 1. The stents prepared in Examples 1-4 and Comparative Examples 1-5 were subjected to mechanical strength tests:
[0146] After the stent is dried, it is placed in an INSTON test machine (34sc -5 ) with a compression speed of 1 mm / min, and the mechanical properties of the scaffold were analyzed.
[0147] Figure 1 is the compressive strength of the brackets in Examples 1-4 and Comparative Examples 1-5, Figure 1 It can be seen that the modified polycaprolactone scaffolds prepared in Examples 1-4 have a compressive strength higher than 20 MPa. Compared with the conventional polycaprolactone scaffold in Comparative Example 5, the compressive strength is significantly improved. Compared with the scaffolds in Comparative Examples 1, 2 and 4 to which only a single hydrogel is added or no composite hydrogel is added, the compressive strength is improved to varying degrees, indicating that the present invention effectively enhances the mechanical properties of the polycaprolactone scaffold by adding a composite hydrogel containing a hydrogel solution and ZIF-8 surface-modified polyester microspheres.
[0148] 2. In vitro cytotoxicity evaluation of the scaffolds prepared in Examples 1-4 and Comparative Examples 1-5:
[0149] The test was carried out in accordance with GB / T 16886.5-2017 “Biological evaluation of medical devices Part 5: In vitro cytotoxicity test”.
[0150] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared to a density of 1.0×10 5 / mL, inoculated in a 96-well plate, 100μL per well. After the cells grow into a monolayer, remove the original culture medium, add 100μL of test sample extract, blank control solution, positive control solution and negative control solution, 6 replicates per group. After the addition of samples, place the 96-well plate at 37℃, 5% CO 2 Incubate in the incubator for 24 hours. After 24 hours, aspirate the original culture medium, add 50 μL 1 mg / mL MTT to each well, and continue to culture for 2 hours. After the end, aspirate the supernatant and add 100 μL 99.5% pure isopropanol to dissolve the crystals; measure the absorbance value on the microplate reader with 570 nm as the main absorption wavelength and 650 nm as the reference wavelength to calculate the cell survival rate.
[0151] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD570 b
[0152] In the formula, OD 570e OD is the average optical density of the test sample or control sample extract; 570b is the average optical density of the blank.
[0153] Table 1 In vitro cytotoxicity evaluation results of the scaffolds in Examples 1-4 and Comparative Examples 1-5
[0154] Group Survival rate (%) Group Survival rate (%) Blank control group 100 Example 4 82.93 Negative control group 84.54 Comparative Example 1 82.27 Positive control group 15.35 Comparative Example 2 82.72 Example 1 83.67 Comparative Example 3 85.65 Example 2 84.23 Comparative Example 4 82.35 Example 3 86.23 Comparative Example 5 81.26
[0155] Table 1 shows the in vitro cytotoxicity evaluation results of the scaffolds in Examples 1-4 and Comparative Examples 1-5. It can be seen from Table 1 that the modified polycaprolactone scaffold provided by the present invention has low in vitro cytotoxicity, the cell survival rate generally reaches more than 82%, and the biosafety is relatively high.
[0156] 3. Hemolytic performance test of the stents prepared in Examples 1-4 and Comparative Examples 1-5:
[0157] According to the amount of blood used in the experiment, collect blood from healthy rabbit hearts. If 10 mL of blood is collected, add 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L to prepare fresh anticoagulated rabbit blood. Take 8 mL of fresh anticoagulated rabbit blood and dilute it with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. Add the test sample to the test group according to the extraction ratio, and then add 10 mL of sodium chloride injection. Add 10 mL of sodium chloride to each tube of the negative control group and 10 mL of distilled water to each tube of the positive control group. Each group operates 3 tubes in parallel. After all test tubes are placed in a constant temperature water bath at (37±1)℃ for 30 minutes, add 0.2 mL of diluted rabbit blood to each test tube, mix gently, and continue to keep warm in a (37±1)℃ water bath for 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes. Aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545nm using a spectrophotometer. The absorbance of the test group and the control group is the average value of three tubes. The absorbance of the negative control tube should not be greater than 0.03, and the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated.
[0158] The formula for calculating the hemolysis rate is: Hemolysis rate (%) = (absorbance of the test sample group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) * 100%
[0159] Table 2 Hemolytic performance test results of the stents in Examples 1-4 and Comparative Examples 1-5
[0160]
[0161]
[0162] Table 2 shows the hemolytic performance test results of the stents in Examples 1-4 and Comparative Examples 1-5. It can be seen from Table 2 that the hemolytic rates of the modified polycaprolactone stents provided by the present invention are all less than 5%, and there is no hemolytic risk.
[0163] 4. In vitro osteogenic differentiation test of pre-osteoblasts induced by the scaffolds prepared in Examples 1-4 and Comparative Examples 1-5
[0164] After irradiation sterilization, the scaffolds prepared in Examples 1-4 and Comparative Examples 1-5 were immersed in DMEM basal culture medium at a concentration of 10 mg / mL and placed in a 37°C shaker at 120 rpm for 24 hours. After the extraction, the mixture of the scaffold and the culture medium was centrifuged at 1000 rpm and the supernatant was collected. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.
[0165] MC3T3-E1 cells were plated at 1×10 5 The cells were seeded at a density of 100 μg / ml in a 24-well plate and the conditioned medium was replaced after 24 h of adherence culture.2 The cells were cultured in an incubator. The culture medium was changed every 2-3 days. After 7 days of culture, the osteogenic differentiation performance was detected by alkaline phosphatase secreted by MC3T3-E1 cells. The pNPP method was used for determination. The specific steps were as follows: After the cells were washed with PBS solution, they were immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol). After the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixture was placed at 37°C for 30 minutes. Subsequently, the mixture was added dropwise to a 96-well plate, and the absorbance of each well at a wavelength of 405 nm was measured using an ELISA reader.
[0166] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH = 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze p-nitrophenyl phosphate chromogenic substrate to produce 1 μmol p-nitrophenol per minute is defined as one enzyme activity unit, also known as one DEA enzyme activity unit. In glycine buffer at pH = 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze p-nitrophenyl phosphate chromogenic substrate to produce 1 μmol p-nitrophenol per minute is defined as one enzyme activity unit, also known as one Glycine enzyme activity unit. One Glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. According to the definition of enzyme activity, calculate the alkaline phosphatase activity in the sample.
[0167] Figure 2 is the alkaline phosphatase activity of the scaffolds in Examples 1-4 and Comparative Examples 1-5, Figure 2 It can be seen that the modified polycaprolactone scaffolds prepared in Examples 1-4 all have a good effect of inducing cells to secrete alkaline phosphatase. The scaffold in Comparative Example 3 does not contain bioactive ceramics, and its osteogenic activity is slightly reduced. The scaffolds in Comparative Examples 1 and 2 do not contain ZIF-8 surface-modified polyester microspheres, and their osteogenic activity is significantly reduced. The scaffolds in Comparative Examples 4 and 5 contain neither ZIF-8 surface-modified polyester microspheres nor bioactive ceramics, and their osteogenic activity is the lowest.
[0168] 5. Antibacterial performance test of the stents prepared in Examples 1-4 and Comparative Examples 1-5:
[0169] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a diluent (0.03 mol / L PBS (pH = 7.2-7.4) containing 1% peptone) to a bacterial count of 5 × 10 5 -10×10 6cfu / mL bacterial suspension. Place the scaffold samples in sterile plates, add 50μL of bacterial suspension to each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60min after adding bacteria, and place the sample in a 5mL nutrient broth tube. Incubate the blood plate and broth tube inoculated with bacteria at 37℃ for 48h, observe the preliminary results, and continue to culture in the sterile growth tube until the 28th day. If the broth tube is turbid and the blood plate has bacterial growth, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).
[0170] Table 3 Antibacterial performance test results of the stents in Examples 1-4 and Comparative Examples 1-5
[0171] Group Staphylococcus aureus Escherichia coli Example 1 - - Example 2 - - Example 3 - - Example 4 - - Comparative Example 1 + + Comparative Example 2 + + Comparative Example 3 - - Comparative Example 4 + + Comparative Example 5 + +
[0172] Table 3 shows the antibacterial performance test results of the stents in Examples 1-4 and Comparative Examples 1-5. It can be seen from Table 3 that the modified polycaprolactone stents prepared in Examples 1-4 all have good long-term antibacterial effects and can grow aseptically for 35 days. However, in Comparative Examples 1, 2, 4 and 5, since the stents do not contain ZIF-8 surface-modified polyester microspheres, it is impossible to use the rapid release of Zn in the acidic microenvironment of bacterial infection. 2+ and 2-methylimidazole exerted their antibacterial effects, and bacterial growth occurred on the 28th day of culture.
Claims
1. A modified polycaprolactone stent, characterized in that: The preparation method comprises the following raw materials: polycaprolactone, bioactive ceramics, solvent I and composite hydrogel; the composite hydrogel comprises a hydrogel solution and ZIF-8 surface-modified polyester microspheres dispersed therein.
2. The modified polycaprolactone stent according to claim 1, characterized in that: The ratio of the polycaprolactone, the bioactive ceramic and the solvent I is 10 g: (0.1-0.5) g: (20-250) mL.
3. The modified polycaprolactone stent according to claim 1, characterized in that: In the composite hydrogel, the concentration of the hydrogel solution is 10-30 mg / mL; And / or, the solid-to-liquid ratio of the ZIF-8 surface modified polyester microspheres to the hydrogel solution is (10-80) mg:1 mL.
4. The modified polycaprolactone stent according to claim 3, characterized in that: The composite hydrogel comprises the following preparation raw materials: hydrogel, degradable polyester, zinc salt, organic ligand, surfactant, photoinitiator, buffer, water and solvent II, wherein the solvent II is the same as or different from the solvent I.
5. The modified polycaprolactone stent according to claim 4, characterized in that: The composite hydrogel is prepared by a method comprising the following steps: The degraded polyester is mixed with solvent II, and added into a mixed solution of surfactant and water to obtain polyester microspheres; The polyester microspheres are added to a mixture of an organic ligand and water, and a mixture of a zinc salt and water is added dropwise to obtain ZIF-8 surface-modified polyester microspheres; The hydrogel is added into a mixed solution of a photoinitiator and a buffer solution to obtain a hydrogel solution, which is then mixed with the ZIF-8 surface-modified polyester microspheres to obtain the composite hydrogel.
6. The modified polycaprolactone stent according to claim 5, characterized in that: In the preparation of the composite hydrogel, the solid-liquid ratio of the degradable polyester to the solvent II is 1 mg:(5-20) mL; And / or, the solid-liquid ratio of the surfactant to water is (0.1-5) g:100 mL; And / or, the solid-liquid ratio of the organic ligand to water is (20-50) mg:1 mL; and / or, the solid-to-liquid ratio of the mixed solution of the polyester microspheres, the organic ligand and water is (5-35) mg:1 mL; And / or, the solid-to-liquid ratio of the zinc salt to water is (3-15) mg:1 mL; And / or, the volume ratio of the mixed solution of the organic ligand and water to the mixed solution of the zinc salt and water is (2-10):1; and / or, in the mixture of the photoinitiator and the buffer solution, the content of the photoinitiator is 0.1-0.5wt%; And / or, the solid-to-liquid ratio of the mixed solution of the hydrogel, the photoinitiator and the buffer solution is (10-30) mg:1 mL.
7. The method for preparing the modified polycaprolactone stent according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, dissolving polycaprolactone in solvent I, adding bioactive ceramics to obtain a bioactive ceramic / polycaprolactone solution, and drying to obtain a bioactive ceramic / polycaprolactone film; S2, placing the bioactive ceramic / polycaprolactone film into a 3D printing barrel, and printing layer by layer to obtain a bioactive ceramic / polycaprolactone scaffold; S3, immersing the bioactive ceramic / polycaprolactone scaffold in the composite hydrogel and solidifying it to obtain the modified polycaprolactone scaffold.
8. The preparation method according to claim 7, characterized in that: The printing parameters include at least one of the following parameters: 1) The needle diameter is 0.1-0.5mm; 2) The barrel temperature is 60-100°C; 3) The needle temperature is 60-100°C; 4) The fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm; 5) Printing speed is 3-15mm / s; 6) The fiber orientation is 0°-90°; 7) Air pressure is 300-400 kPa; 8) The layer height of the bioactive ceramic / polycaprolactone scaffold is 80%-90% of the needle diameter.
9. The preparation method according to claim 7, characterized in that: The solid-liquid ratio of the bioactive ceramic / polycaprolactone scaffold to the composite hydrogel is (0.3-1.2) mg:10 mL.
10. The preparation method according to claim 7, characterized in that: The soaking time is 0.5-5min; And / or, the curing condition is 400-410nm blue light irradiation for 2-15s.
Citation Information
Cited By
Bioactive poly (p-dioxanone)-based composite material as well as preparation method and application thereof
CN121796686A